Precise spectroscopic parameters for solar-type stars with moderate-to-high rotation. Issue 67 (17th July 2015) - Tsantaki, M.; Sousa, S.; Santos, N.C.; Montalto, M.
Abstract : One of the primary objectives of Gaia is to survey billions stars and build the most precise 3D map of the Milky Way. Automated techniques of spectral analysis are needed to perform a rapid and homogeneous processing of the data to provide precise and accurate stellar parameters, such as for the GAIA-ESO survey. In this context, our recent work is based on the spectral synthesis technique to derive parameters for both slowly and fast rotating stars (Tsantaki et al. 2014). The spectroscopic analysis was performed using the package Spectroscopy Made Easy (SME; Valenti & Piskunov 1996) and a specific methodology to deal with fast rotators (υsini up to 50 km/s). The spectral regions, including the atomic data of all the lines in our analysis are available online in SME readable formathttp://mariatsantaki.weebly.com . A comparison between the parameters derived with our methodology and with the iron ionization and excitation method ( e.g. Sousa et al. 2008; Tsantaki et al. 2013) shows that both results are on the same scale. Additionally, for fast rotating stars, our results are in good agreement with literature values when comparing to other methods. We are now able to provide parameters for a very wide group of stars: from giants to dwarfs and from slowly to fast rotating stars. Except for galactic studies, stellar parameters are important for the planetary characterization. We provided updated stellar and planetary properties for ten systems. The stellar parameters were compiled in the SWEET-Catalogue (https://www.astro.up.pt/resources/sweet-cat/ ).